Streamlining Natural Products Biomanufacturing With Omics and Machine Learning Driven Microbial Engineering - Ramzi, Ahmad Bazli; Baharum, Syarul Nataqain; Bunawan, Hamidun; Scrutton, Nigel S. (Frontiers in Bioengineering and Biotechnology, 2020)
Increasing demands for the supply of biopharmaceuticals have propelled the advancement of metabolic engineering and synthetic biology strategies for biomanufacturing of bioactive natural products. Using metabolically-engineered microbes as the bioproduction hosts, a variety of natural products including terpenes, flavonoids, alkaloids and cannabinoids, have been synthesized through the construction and expression of known and newly-found biosynthetic genes primarily from model and non-model plants. The employment of omics technology and machine learning platforms as high throughput analytical tools has been increasingly leveraged in promoting data-guided optimization of targeted biosynthetic pathways and enhancement of the microbial production capacity thereby representing a critical debottlenecking approach in improving and streamlining natural products biomanufacturing. To this end, this mini review summarizes recent efforts that utilize omics platforms and machine learning tools in strain optimization and prototyping and discusses the beneficial uses of omics-enabled discovery of plant biosynthetic genes in the production of complex plant-based natural products by bioengineered microbes.